Effect of ambient temperature on daily hospital admissions for acute pancreatitis in Nanchang, China: A time-series analysis. Issue 10 (3rd October 2022) - Li, Bozhen; Huang, Wenzhong; Chen, Pengguo; Chen, Jianyong; Biviano, Ivano; Wang, Zhaohan
ABSTRACT: The aim of this study was to evaluate the short-term effect of temperature on the risk of acute pancreatitis (AP) in southern China. We performed a time-series study of 2822 patients admitted with a first episode of AP in Nanchang between May 2014 and June 2017. A generalized additive model combined with a distributed lag non-linear model was applied to assess the association of temperature and AP. In subgroup analysis, according to different etiologies of pancreatitis, significant associations were found between daily average temperature and non-biliary pancreatitis hospitalization at lags of 0–7 days, but not for biliary pancreatitis or total AP. Higher daily average temperature tended to increase the occurrence of non-biliary pancreatitis at lags of 0–7 days. These findings suggest that high temperature is associated with higher non-biliary pancreatitis risk in Nanchang, China. In the context of global warming, the morbidity of non-biliary pancreatitis may increase.